Optimization of a Marine Fish Release Strategy: A Case Study of Black Sea Bream Acanthopagrus schlegelii in the Zhanjiang Estuary, Northern South China Sea - Zhang, Shenzeng; Lin, Lin; Wang, Xuefeng (Frontiers in Environmental Science, 2021)
Releasing strategy ( the choice of preferable releasing type, mode, time, scale and sites ) is an important part of quantitative evaluation on the fish stocking enhancement, and the optimization of releasing strategy provides an effective insights on the stocking work to achieve the goal of alleviating the decline of fishery resources and increasing the income of fishermen. In this study, a typical released fish black sea bream Acanthopagrus schlegelii in the northern South China Sea, was taken as the research object. Combining the biological characteristics of Acanthopagrus schlegelii in Zhanjiang sea area during June, July, September,2000 to April 2021, its standard length frequency and its growth parameters were estimated using the ELEFAN I method of FiSAT II. We then simulated and evaluated the effects of five scenarios due to different releasing strategies, assuming the fixed total quantity of released fish and the constant of mortality rate at stages . Results showed that: 1) The breeding peak period of black sea bream was concentrated mainly from December to March of the next year, which was also most significant period on the the sexual reversal occurring . 2) The relationship between length and weight of black sea bream is y = 5.092×10-5 x2.906, L∞ = 54.39 cm, K = 0.15, t0 = -0.967. 3) The suitable releasing period of black sea bream in Zhanjiang estuary is from June to October. It is preferrable and more productive if the the total quantity of releasing fish can be divided into two batches. In this study, the growth potential of juvenile released fish was evaluated based on the density-dependent theory, and the stock enhancing effect of released stocks was simulated and analyzed with biological parameters and field sampling techniaque, which provided a reference for the optimization of fish releasing strategy in coastal waters.